Prevalence of Coronary Artery Disease Among Patients Presenting with Chest Pain of Suspected Cardiac Origin at A Tertiary Care General Hospital in Gandaki Province of Nepal - Koirala, Pragati; Saha, Chanchu Gopal (Nepalese Heart Journal, 2025)
Background and Aim: The prevalence of coronary artery disease among patients presenting with chest pain of suspected cardiac origin in western part of Nepal is not known. We aimed to study the prevalence of coronary artery disease among patients presenting with chest pain of suspected cardiac origin in an emergency department of a general tertiary care hospital in Gandaki province of Nepal. Methods: This was a prospective cross-sectional study conducted over a period of 5 months that included all patients aged 16 years and above presenting to the emergency department with acute chest pain of suspected or diagnosed cardiac origin. The primary outcome measure was to calculate the prevalence of coronary artery disease and secondary outcome measures included identification of common ECG changes in such patients and the relationship of such changes with the provisional diagnoses of the patients. Results: One hundred fifty patients were enrolled in the study. The prevalence of coronary artery disease was 44% (66/150) among those patients with chest pain of cardiac origin. T wave inversion was the most prevalent ECG change (44%), followed by ST-T segment depression (28%), Left bundle branch block 11.33%, ST segment elevation 10.66%, left ventricular hypertrophy 10%. Pathological Q waves were present in 6.66% and poor R-wave progression was seen in 3% of the patients. ECG had high diagnostic accuracy to detect ischaemia. Conclusion: The prevalence of coronary artery disease among patients with chest pain of suspected cardiac origin in the emergency department of tertiary care general hospital is around 44%. The common ECG changes are ST depression and T wave inversion. ECG detected most of the myocardial ischaemia in the emergency department.